Green Strategies for Insect Pest Management in Natural Dye Yielding Trees - Rajashekhar, M.; Ramanjaneyulu, A. V.; Pooja, S. Lakshmi; Chaitanya, T.; Deepthi, S. Sirisha; Rahul, Ch.; Abhyudaya, U. J.; Priyanka, N. (Chronicle of Bioresource Management, 2025)
Natural dye-yielding plants, essential for sustainable and eco-friendly colorant production, are increasingly vulnerable to insect pest infestations that compromise not only dye quality but also crop yield. The reliance on conventional synthetic insecticides for pest management poses significant challenges, including environmental contamination, adverse effects on non-target organisms, and the accumulation of toxic residues, which fundamentally conflict with the environmentally sustainable principles of crop management. Sustainable and eco-friendly pest management practices such as biological control, botanical insecticides, cultural and mechanical practices offer effective alternatives. Adoption of Integrated Pest Management (IPM) combining these eco-friendly approaches but excluding pesticides can not only help in environmental sustainability, but also safeguard the tree health, besides preserving biodiversity and ecological integrity. This transition is essential for advancing natural dye production and supporting environmentally conscious markets. The present paper discusses major pests affecting natural dye yielding trees and pro-environmental strategies for managing the same.